2023
DOI: 10.3389/fimmu.2023.1254759
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic investigation of Nordic patients with complement-mediated kidney diseases

Viktor Rydberg,
Sigridur Sunna Aradottir,
Ann-Charlotte Kristoffersson
et al.

Abstract: BackgroundComplement activation in atypical hemolytic uremic syndrome (aHUS), C3 glomerulonephropathy (C3G) and immune complex-mediated membranoproliferative glomerulonephritis (IC-MPGN) may be associated with rare genetic variants. Here we describe gene variants in the Swedish and Norwegian populations.MethodsPatients with these diagnoses (N=141) were referred for genetic screening. Sanger or next-generation sequencing were performed to identify genetic variants in 16 genes associated with these conditions. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Our group has previously shown that monozygotic twins with a gain-of-function variant in CFB , encoding complement factor B, differed regarding the development of aHUS [ 24 ]. Moreover, the same genetic variant may be associated with aHUS in one individual and C3 glomerulopathy in another [ 28 ]. In addition to genetic composition, other factors may play a role, such as environmental exposures (i.e., vaccinations and infections.)…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously shown that monozygotic twins with a gain-of-function variant in CFB , encoding complement factor B, differed regarding the development of aHUS [ 24 ]. Moreover, the same genetic variant may be associated with aHUS in one individual and C3 glomerulopathy in another [ 28 ]. In addition to genetic composition, other factors may play a role, such as environmental exposures (i.e., vaccinations and infections.)…”
Section: Discussionmentioning
confidence: 99%